Effect of Information Technology Utilization and Audit Techniques on Audit Quality: Evidence from External Auditors - Nur Aliah; Eni Duwita Sigalingging (PT. Riset Press International, 2026)
This study aims to analyze the impact of the use of information technology and audit techniques on audit quality among external auditors in Medan, Indonesia. This study employs a quantitative approach using primary data collected through a questionnaire distributed to auditors working at Public Accounting Firms in the city of Medan. The sampling technique used nonprobability sampling with a sample size of 40 auditors. The collected data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that the utilization of information technology has a positive and significant effect on audit quality. This suggests that the use of technology enhances efficiency, accuracy, and the scope of audit testing. Audit techniques also have a positive and significant effect on audit quality, indicating that the application of appropriate and systematic audit procedures plays a crucial role in producing high-quality audits. This study provides an empirical contribution to enriching the auditing literature, particularly regarding the integration of information technology and audit techniques in improving audit quality. The practical implication of this study is the importance for auditors and Public Accounting Firms to enhance their competencies in utilizing technology and applying audit techniques that align with the evolving modern audit environment.